Institutions versus Policies: A Tale of Two Islands - Henry, Peter Blair; Miller, Conrad (American Economic Review, 2009)
Recent work emphasizes the primacy of differences in countries’ colonially-bequeathed property rights and legal systems for explaining differences in their subsequent economic development. Barbados and Jamaica provide a striking counter example to this long-run view of income determination. Both countries inherited property rights and legal institutions from their English colonial masters yet experienced starkly different growth trajectories in the aftermath of independence. From 1960 to 2002, Barbados’ GDP per capita grew roughly three times as fast as Jamaica’s. Consequently, the income gap between Barbados and Jamaica is now almost five times larger than at the time of independence. Since their property rights and legal systems are virtually identical, recent theories of development cannot explain the divergence between Barbados and Jamaica. Differences in macroeconomic policy choices, not differences in institutions, account for the heterogeneous growth experiences of these two Caribbean nations.